Improved ammonia sensitivity and broadband photodetection by using PBTTT-C14/WS2-QDs nano-heterojunction based thin film transistor - Gupta S.; Pal B.N.; Prakash R. (My University, 2025)
An ambient temperature broadband photo-detector and ammonia (NH3) gas sensor devices are developed with PBTTT-C14/WS2-QDs heterojunction thin film. This composite thin film of PBTTT-C14 conjugate polymer and hydrothermally synthesized WS2-QDs have been deposited by high yield and cost-effective ‘floating film transfer method’ (FTM), which works as a channel (p-type) of the thin film transistor (TFT). To determine the NH3 sensing behavior of the TFT, different concentrations of analyte (0.5–20 ppm) have been exposed on the channel of the TFT, which shows the response of ∼ 50 % at 10 ppm ammonia concentration that is significantly higher than PBTTT-C14 only TFT. This improvement is made possible by the NH3-responsive depleted layer of polymer/QDs heterojunction, which varies widely in the presence of ammonia. As a consequence, the ON/OFF ratio, carrier mobility and threshold voltage (Vth) of the device changes in a wider range. Besides, this TFT based gas sensor is also highly selective to the other interfering gases. In addition to NH3 gas sensitivity, This TFT also shows very high photosensitivity under white light illumination that enhances ‘ON’ and ‘OFF’ current of the device by ∼ 2.2 and 70 times, respectively under one sun white light illumination, whereas Vth of the device is shifted by ∼ 22 V. Besides, the device shows quite fast response/ recovery time under NH3 gas exposure and light illumination. © 2024 Elsevier B.V.